Editorial: The Heart of Learning: Embracing Change in Education With Empathy and Innovation - Thomas D. Dyer (Journal of Scholarly Engagement)
The educational landscape is experiencing a period of transformation, shaped by advancements in technology, shifts in student demographics, and the ever-growing emphasis on well-being and inclusivity. As we navigate these changes, it is essential to reflect on the trends driving the evolution of pedagogy and institutional practices. According to Mowreader (2023) faculty and administrators are grappling with how to best implement technological tools while maintaining student engagement and academic integrity. One prominent examp0le is the increased use of artificial intelligence (AI) in both administrative tasks and instructional design. While AI has the potential to streamline processes, it also brings challenges in ensuring ethical use and maintaining human-centered teaching. In an era where AI is rapidly transforming the educational landscape, one thing remains constant: good teaching, at its core is social. While AI offers new tools and possibilities, it does not replace the fundamental elements that define effective education.